2018
DOI: 10.1021/acscatal.8b00666
|View full text |Cite
|
Sign up to set email alerts
|

Structural Dynamics and Catalytic Properties of a Multimodular Xanthanase

Abstract: The precise catalytic strategies used for the breakdown of the complex bacterial polysaccharide xanthan, an increasingly frequent component of processed human foodstuffs, have remained a mystery. Here we present the characterization of an endo-xanthanase from Paenibacillus sp. 62047. We show that it is a CAZy family 9 glycoside hydrolase (GH9) responsible for the hydrolysis of the xanthan backbone, capable of generating tetrameric xanthan oligosaccharides from polysaccharide lyase family 8 (PL8) xanthan lyase-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Surprisingly, the NMR analysis suggested that Ru GH5a cleaves XG at the reducing end of the non-branching backbone glucosyl residue ( Figure 3c, Extended Data 7 ). This contrasts with the product of other known xanthanases (such as the GH9 from Paenibacillus nanensis 35 or the β-D-glucanase in Bacillus sp. strain GL1 15 ), which hydrolyze xanthan at the reducing end of the branching glucose, demonstrating a hitherto unknown enzymatic mechanism for the degradation of XG.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Surprisingly, the NMR analysis suggested that Ru GH5a cleaves XG at the reducing end of the non-branching backbone glucosyl residue ( Figure 3c, Extended Data 7 ). This contrasts with the product of other known xanthanases (such as the GH9 from Paenibacillus nanensis 35 or the β-D-glucanase in Bacillus sp. strain GL1 15 ), which hydrolyze xanthan at the reducing end of the branching glucose, demonstrating a hitherto unknown enzymatic mechanism for the degradation of XG.…”
Section: Introductionmentioning
confidence: 74%
“…strain GL1 15 ), which hydrolyze xanthan at the reducing end of the branching glucose, demonstrating a hitherto unknown enzymatic mechanism for the degradation of XG. While Ru GH5a displayed little activity on other polysaccharides ( Extended Data 6 ), it was able to hydrolyze both native and lyase-treated XG with comparable specificity, once more in contrast to most previously known xanthanases, which show ≥600-fold preference for the lyase-treated substrate 35 ( Figure 3d ). One exception is the xanthanase from Microbacterium sp.…”
Section: Introductionmentioning
confidence: 86%
“…This endo-xanthanase is able to attack the backbone of XL-treated xanthan and possesses a CD belonging to glycoside hydrolase family 9 along with four additional domains constituted largely of b sheets. The latter of these corresponds to the module identified here, and has now been shown to bind xanthan, becoming the founding member of CBM family 84 (Moroz et al, 2018). Structurally related to CBM6, CBM35, and CBM36, the structure of PXL CBM84 is shown in Figure 2.…”
Section: Crystal Structure Of Pxlmentioning
confidence: 65%
“…As seen in the Results section, CBM84 is essential for full activity by PXL. Interestingly, truncation of the corresponding module did not impair the activity of the endo-xanthanase in Moroz et al (2018). Since initial sequence analysis indicated a relationship of CBM84 and X to CBM35, which are related to CBM6 and CBM36, pairwise structural similarity comparisons were carried out for both modules against all representatives of CBM6, CBM35, and CBM36.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation